Formwork Support Design of Roof of Subway Interval Engineering Based on Finite Element Analysis - Li, Sujuan (Manufacturing Technology Journal, 2019)
The design of the formwork support for a certain section of the Beijing subway project was carried out in this paper. And the disk lock formwork support was used in the engineering.It was analyzed on the the design of the formwork support for the roof with the thickness of 1.5m of the interval engineering. The manual calculation and the sap2000 finite element analysis were also used in the paper.The effect of the diagonal brace and its number were analyzed in addition to the design of the formwork support. It was showed that the axial force of the standing tube tends to be uneven with the increase of the number of slant bars in the framework. And the axial force of the standing tube connected to diagonal brace is larger than that of the framework without brace significantly. So it will be dangerous to the framework without considering the effect of it by the manual calculation.
Keywords: Disk Lock; Formwork Support; Steel Tubular Scaffold; Finite Element Analysis